(3dhGeY GdCSQGQ TQM eWGdY GdCSQGQs - (3GdQGRj, GdbWH GdJMJGfj, eMeO Hf eMeO, (B766 (3g`s
(3ChdgG (B:s
(3bGd GdbSe GdKGfj aj GcJSGH GdJUOjbGJ Cbhd Cj GdeLghdGJ GdJUOjbjIs
(3BNQgG (B:s
(3Ke YQV dg GdZdW aj GdacQ agh LOjQ HCf jgLQ GdMceI dG jchf eSJYO dOQc MbGFb GdCTjGA hcd ejSQ deG Ndb dgs
(3efbhdI ef fSNI GdeDda GdeDNQI SfI (B728 (3g` HeOjfI JHQjRs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 38s
(3eYLe GdeDdajf (B3 / 642s
(3cTa GdXfhf (B2 / 1716s
(3TPQGJ GdPgH (B6 / 207s
Keywords: (3GdadSaI hGdefWbs